Our blue planet; the story of the earth's evolution. - Haber, Heinz (New York, Scribner, 1969)
Describes the origin of the earth, its internal structure, the formation of atmosphere and oceans, and the development of climates.
Translation of Unser blauer Planet.
Keywords: Earth (Planet); Earth (Planet)